Deposition of artificial radionuclides in sediments of Loch Etive, Scotland. (July 2018) - Al-Qasmi, Hamza; Law, Gareth T.W.; Fifield, L. Keith; Howe, John A.; Brand, Tim; Cowie, Gregory L.; Law, Kathleen A.; Livens, Francis R.
Abstract: The nuclear fuel reprocessing plants on the Sellafield site (UK) have released low-level effluents into the Irish Sea under authorisation since 1952. This has led to the labelling of nearby offshore sediments with a range of artificial radionuclides. In turn, these sediments act as a long-term secondary source of both soluble and particle-associated radionuclides to coastal areas. These radionuclides are of interest both in assessing possible environmental impacts and as tracers for marine processes. Here we present results from a study of the geochemistry of natural ( 234, 238 U) and artificial ( 137 Cs, 241 Am, 238 Pu, 239+240 Pu, and 236 U) radionuclides and their accumulation in sediments from Loch Etive, Scotland. The data are interpreted in the context of the historical radioactive discharges to the Irish Sea and biogeochemical processes in marine sediments. Loch Etive is divided into two basins; a lower, seaward basin where the sedimentation rate (∼0.6 cm/yr) is about twice that of the more isolated upper basin (∼0.3 cm/yr). These accumulation rates are consistent with the broad distribution of 137 Cs in the sediment profiles which can be related to the maximum Sellafield discharges of 137 Cs in the mid-1970s and suggest that 137 Cs was mainly transported in solution to Loch Etive during that period. Enrichments of Mn, Fe, and Mo in sediment and porewater from both Loch Etive basins result from contemporary biogeochemical redox processes. Enrichments of 238 U and 234 U in the lower basin may be a result of the cycling of natural U. By contrast, the Sellafield-derived artificial isotope 236 U does not seem to be affected by the redox-driven reactions in the lower basin. The 238 Pu/ 239, 240 Pu ratios suggest contributions from both historical Sellafield discharges and global fallout Pu. The uniform sediment distributions of Pu and Am, which do not reflect Sellafield historical discharges, suggest the existence of a homogenous secondary source. This could be the offshore 'mud patch' in the vicinity of Sellafield from which the supply of radionuclides reflects time-integrated Sellafield discharges. This source could also account for the continuing supply of Cs to Loch Etive, even after substantial reductions in discharge from the Sellafield site. Highlights: Sellafield is the dominant source of artificial radionuclides in the NE Irish Sea. Offshore sediments close to Sellafield act as a secondary source of radionuclides. Enrichments of 238 U and 234 U could be a result of the redox cycling of natural U. Artificial radionuclides are not significantly affected by redox chemistry in this system.